Ownership and hibah issues of Takaful benefit - Mohd Noor, Azman; Abdullah, Mohamad Asmadi (IIUM Institute of Islamic Banking and Finance, 2009)
This paper aims at investigating the ownership of the Takaful benefit and the issues of hibah in nomination. The focus is made solely on the Family takaful because this type of policy is singularly related to death. In this regard, the question is raised as whether the money paid by the Takaful operator on the death of the participant (death benefit) before the policy matures constitutes the participant's estate or not, and secondly over the validity of making a conditional hibah of that takaful policy to a nominee as a sole beneficiary.